2021
DOI: 10.1590/1518-8345.4975.3474
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with chemsex in Portugal during the COVID-19 pandemic

Abstract: Objective: to investigate the factors associated with the practice of sex under the influence of drugs (chemsex) among Portuguese men who have sex with men during the period of social distancing to prevent the COVID-19. Method: online survey applied in May 2020 to a sample of 1,301 participants living in Portugal, recruited according to Respondent Driven Sampling and via social media Facebook®. Descriptive and bivariate analyses were performed along with logistic regression to calculate adjusted Odds Ratio (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 37 publications
0
34
0
6
Order By: Relevance
“…Although they are countries with striking social, cultural and political differences, previous studies (18)(19)(20)28) have shown that Brazilian and Portuguese MSM present similar sexual behaviors and practices that deserve more in-depth analysis, especially from the perspective of global health. Thus, this study conveys in a convergent manner the need for knowledge translation in order to guide professional conduct in health and nursing for adolescents residing in both countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are countries with striking social, cultural and political differences, previous studies (18)(19)(20)28) have shown that Brazilian and Portuguese MSM present similar sexual behaviors and practices that deserve more in-depth analysis, especially from the perspective of global health. Thus, this study conveys in a convergent manner the need for knowledge translation in order to guide professional conduct in health and nursing for adolescents residing in both countries.…”
Section: Discussionmentioning
confidence: 99%
“…The adolescents who were part of the sample were recruited online through two strategies. The first was snowball sampling, adapted to the virtual environment and consolidated by other studies (16)(17)(18)(19)(20) . Through this method, the participants themselves are responsible for recruiting other individuals in similar situations through their social and contact networks.…”
Section: Data Collectionmentioning
confidence: 99%
“…The expert analysis covered the questionnaire's construct validity and its cultural and linguistic properties. The online questionnaire was hosted on a specific website that allowed for quick data collection in Brazilian and European Portuguese and only allowed one response via Internet Protocol (IP), that is, one response per electronic device, thus avoiding multiple entries by the same user and, consequently, selection biases [18,19].…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), a respiratory disease caused by the etiologic agent SARS-CoV-2, which is registered in 178 countries, has produced, or intensified what the WHO has called the "infodemic" [1], a term used to characterize the uncontrolled volume of information disseminated on a subject, including real and fake news. Excessive information makes it difficult to discern reliable sources and obtain safe guidelines for actions [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the male population is less likely to adhere to COVID-19 prevention measures and be more involved in health risk behaviors than women [13,14]. Men are more likely to participate in large public meetings or have close physical contact with others [15][16][17]. They also tend to have lower rates of handwashing, social distancing, and wearing masks [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%